INFLUENCE OF WORD OF MOUTH AND PRODUCT QUALITY ON PURCHASE DECISIONS AND REPURCHASING INTEREST - Ali Ahmad Yasin; Gusti Noorlitaria Achmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to analyze and explain the influence of word of mouth and product quality on purchasing decisions and repurchase intentions; The population in this study are consumers who have visited more than 1 time at Ichiban Sushi BigMall Samarinda. The sampling technique used was non-probability sampling with the purposive sampling method with a total sample of 90 people. Data collection techniques using questionnaires. The analysis was carried out using Partial Least Square (PLS) with the SmartPLS application version 3.8.9 and using SPSS Version 25 to test the validity and reliability of the respondents. The results showed that: Word of Mouth had a positive and significant effect on Purchase Decisions, Word of Mouth had a positive and insignificant effect on Repurchase Interest,